Design, synthesis and biological evaluation of novel O-substituted tryptanthrin oxime derivatives as c-Jun N-terminal kinase inhibitors; Frontiers in Pharmacology; Vol. 13 - Schepetkin (Shchepyotkin) I. A. Igor Aleksandrovich; Kovrizhina A. R. Anastasia Ruslanovna; Stankevich K. S. Ksenia Sergeevna; Khlebnikov A. I. Andrey Ivanovich; Kirpotina L. N. Liliya; Quinn M. T. Mark; Cook M. J. Matthew (2022, 2022)
Title screen